Spirituality and Depression with Self-Moving Trends in Adolescents: (Empirical Evidence in Yogyakarta, Indonesia) - Sri Setyowati; Suyatno Suyatno (International Journal of Health Science and Technology, 2020)
Indonesia is the 14th country with the highest suicide rate in the world and the 8th highest country in ASEAN. Yogyakarta is the city that places the second rank in Indonesia with the highest child and adolescent suicide rates. The purpose of this study is to analyze spirituality and depression with suicidal tendencies in adolescents in Gunung Kidul, Yogyakarta. The method used is of quantitative research using multiple regression. This study found that there is a significant relationship between depression and suicidal tendencies. This study suggests that the need for the role of counselling guidance teachers to improve their guidance and counselling as well as the role of community nurses to optimize their nursing care, especially in adolescents.